Improved Charge Transfer Contribution by Cosputtering Ag and ZnO - Bingbing Han; Shuang Guo; Sila Jin; Eungyeong Park; Xiangxin Xue; Lei Chen; Young Mee Jung (Nanomaterials, 2020)
A two-dimensional polystyrene microsphere array cosputtered with Ag and ZnO was designed for evaluating surface-enhanced Raman scattering (SERS) activity. The surface plasmon resonance (SPR) and SERS properties were significantly changed by the introduction of ZnO into the Ag film. By increasing the Ag sputtering power, a redshift of the SPR peak was obtained. Moreover, improved SERS activity occurred because of the electromagnetic (EM) contribution from the increasing Ag content and the charge transfer (CT) contribution from the introduction of ZnO. More importantly, the Hall effect was employed to evaluate the carrier density effect on the SERS contribution of the Ag/ZnO film. The increase in the carrier density as the Ag sputtering power increased indicated an increasing number of free electrons stored in the Ag/ZnO film, which was accompanied by improved EM and CT contributions.